2016
DOI: 10.1007/s00417-016-3343-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and pathogenesis of paravascular inner retinal defects associated with epiretinal membranes

Abstract: Deviation of retinal vessels due to the traction of the ERMs may contribute to the pathogenesis of PIRDs. PIRDs often cause visual field abnormalities corresponding to the location of the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The 7 ERMs identified in glaucomatous eyes resembled the ERM in the suspect eye in appearance on en-face and in location in the macular region. Similar to the results of Miyoshi et al, 13 ERMs in eyes with PD tended to occur within the temporal arcade and were not continuous with PDs.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The 7 ERMs identified in glaucomatous eyes resembled the ERM in the suspect eye in appearance on en-face and in location in the macular region. Similar to the results of Miyoshi et al, 13 ERMs in eyes with PD tended to occur within the temporal arcade and were not continuous with PDs.…”
Section: Discussionsupporting
confidence: 87%
“…Only 2 of the 11 (18.2%) glaucomatous eyes with PDs had ERMs. While previous studies have shown that eyes with PDs often have ERMs, 1,5,12,13 it is likely due to the fact that both PDs and ERMs have been associated with high myopia. 5 However, in this study, all eyes had a spherical refractive error better than −6D.…”
Section: Paravascular Defectsmentioning
confidence: 90%
See 1 more Smart Citation
“…In both studies, however, there was no mention about full-thickness retinal defects. In addition to high myopia, eyes with ERM also frequently have PVAs, showing similar lesions as those in highly myopic eyes [4]. In our previous study [5], we found that cases with PVAs had significantly greater central macular thickness; the thicker the macula, the more severe the PVA complex.…”
Section: Introductionmentioning
confidence: 54%
“…Various OCT findings were collected, such as central foveal thickness, maximal retinal thickness, retinal contraction, the attenuation or absence of the inner segment/outer segment (IS/OS) junction, attenuation or absence of the external limiting membrane (ELM), and the presence of intraretinal cysts, 12 lamellar holes, pseudoholes, 13 and paravascular inner retinal defects, as previously described 14 ( Fig. 1).…”
Section: Patients and Clinical Data Acquisitionmentioning
confidence: 99%